Penerapan Sustainable Lifestyle Menggunakan Limbah Kulit Bawang Putih dan Kulit Jeruk Menjadi Spray Antiserangga bagi Warga Rusunawa Rorotan, Jakarta Utara - Yumita, Agustin; Delita, Novia; Fujianti, Fujianti (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Every year household waste is the highest contributor. A sustainable lifestyle is an alternative that can be done to reduce it. This activity aims to provide education and improve skills in managing garlic and orange peel waste into insect-repellent sprays for the residents of the Rorotan Rusunawa Flats. The activity began with observations by giving a pre-test form to see how far the participants' understanding was, resource persons providing material, practicing making insect repellent sprays, and finally filling out the post-test form to evaluate activities. This community service activity shows the participants are enthusiastic, as described in the Sig value. 2-tailed sample <0.05, which means there is a significant difference between the pre-test and post-test. The provision of material by resource persons and practice by trainers significantly affected the participants' knowledge and skills.